Business Process Improvement at PT. PLN (Persero) Certification Center - Qoriyana, Farieza; Adhi Utama, Akbar (The Indonesian Journal of Business Administration, 2016)
Abstract. At this time the request for Sertifikat Laik Operasi (SLO) at PT PLN (Persero) Certification Center continues to increase, but the SLO published not optimal. There is occurs because the certification process take a long times for finished the job like looping process still found in the certification process.Â  The longer of certification process will be impact to publishing SLO that will be longer too and its causes pending item each year. To know the causes of certification process takes a long time the first phase is mapping the business process of this company. After mapping the business process then search the root cause using current reality tree diagram. The next phase is solve the problem using Business Process Modeling Notation (BPMN) so the each task will more clearly. The result of this study is to improve the business process in this company more efficient. It can be seen from the lead time that faster than before which is from more than 125 days to 123 days so that the pending item can be finished. In other hand, online system improvement and also coordination between department needed due to this workflow from business process running well. Â Keyword: Business Process, Business Process Improvement, Business Process Modeling Notation (BPMN), Sertifikasi Laik Instalasi/SLO